2021
DOI: 10.3389/fpsyg.2021.646181
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Senses: How Self-Directed Speech and Word Meaning Structure Impact Executive Functioning and Theory of Mind in Individuals With Hearing and Language Problems

Abstract: Many individuals with developmental language disorder (DLD) and individuals who are deaf or hard of hearing (D/HH) have social–emotional problems, such as social difficulties, and show signs of aggression, depression, and anxiety. These problems can be partly associated with their executive functions (EFs) and theory of mind (ToM). The difficulties of both groups in EF and ToM may in turn be related to self-directed speech (i.e., overt or covert speech that is directed at the self). Self-directed speech is tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Since language develops in a comparative manner, the early development of language, EF and ToM plausibly interact in an empowering or inhibitive manner. In this way, recent authors have argued that the deficits in EF and ToM in individuals with DLD can be explained by the problems in the synthetization of language with precursors of EF and ToM (22)(23)(24).…”
Section: The Interplay Between Language Social Communication and Cogn...mentioning
confidence: 99%
“…Since language develops in a comparative manner, the early development of language, EF and ToM plausibly interact in an empowering or inhibitive manner. In this way, recent authors have argued that the deficits in EF and ToM in individuals with DLD can be explained by the problems in the synthetization of language with precursors of EF and ToM (22)(23)(24).…”
Section: The Interplay Between Language Social Communication and Cogn...mentioning
confidence: 99%
“…According to Camminga et al (2021), people with hearing disorders experience social and emotional problems, such as communication difficulties, depression, anxiety and aggression. These problems lead to speech disorders.…”
Section: Corrective-developmental Work On a Communicative Function Of...mentioning
confidence: 99%
“…Also, labeling allows the word and the associated mental image (signified and signifier) to be used separately which allows language to be disengaged from direct perception, enabling more flexible cognition including EF ( Toomela, 2003 ). It’s suggested that in children with developmental language disorder and deaf/hard of hearing children, EF deficits could be related to the mentioned property of language allowing the construction of non-sensory representations resulting from the distinction between signified and signifier ( Camminga et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%